Analisis Perbedaan Abnormal Return Saham Dan Trading Volume Activity Sebelum Dan Sesudah Stock Split Pada Perusahaan Yang Terdaftar Di BEI - Sintya Maharani; Nurjanti Takarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze differences in changes in abnormal stock returns (AR) and trading volume activity (TVA) pre-stock split and post-stock split. It is a quantitative research with a window period of 11 days (event study) consisting of 5 days pre-stock split and 5 days post-stock split. Using the analysis technique Paired sample t-testfor the AR variable and the Wilcoxon signed rank test for the TVA variable. The number of research samples as many as 18 companies listed on the IDX that have carried out stock splits from 2019 to 2021. This study shows that there are differences before and after the stock split on abnormal returns, but there is no difference in trading volume activity both before and after stock splits. Keywords : Abnormal Returns, Stock Splits, Trading Volume Activity